A Study on Identity of Pertev Pasa District in Famagusta, North Cyprus, Considering Urban Design Dimensions - Lotfi, Kamyar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Today, urban design as a multi-dimensional discipline have brought another model of societal variation in contemporary world. It shapes the interface among all the significant issues that are converse to human body and environment by means of obligation to oversee and change the communications of the distinct perspectives of civic life into a social and physical formation. Comprehension of physical and social characteristics of urban environments turn into a contemporary research topic in urban design and architecture. The current study attempts to examine the socio-cultural and socio-economic identity of people living in Pertev Pasa district in Asagi Maras (Kato Varosha), Famagusta, to be able to define what kind of a physical environment they would like to live in in the future. Uncertainties in political issues of the area (to be given back to their original owners or investment for a stable development with the existing inhabitants) brought many social and physical tensions within itself. Determining how urban design could be seen as a solution in social landscape and also the roles of urban design in creating a lively settlement to enrich the life quality and development of urban context, are the aims focused on this research. The methodology of research consist of two main techniques in terms of qualitative and quantitative approach. Literature review, questionnaire survey, interview and observation are used as research methods in collecting data. According to the evaluations on social and physical identity of urban environment in Pertev Pasa, some guidelines are recommended in conclusion based on two scenarios that might happen in the future development of Asagi Maras. Keywords: Identity, Socio-culture, Socio-economy, urban design, Pertev Pasa, Asagi Maras, Famagusta, North Cyprus.

ÖZ: Günümüzde kentsel tasarım çok boyutlu bir disiplin olarak farklı bir toplumsal değişim modelini çağdaş dünyaya taşımıştır. Kentsel tasarım, insan ve çevreyle ilgili her konuda, sosyal ve fiziksel çevre oluşumunu ve değişimini şekillendirmiştir. Kentsel çevrenin fiziksel ve sosyal özelliklerinin kavranması, kentsel tasarım ve mimarlığın, çağdaş araştırma konusu haline gelmiştir. Bu çalışma Kuzey Kıbrıs’ta Gazimağusa kentinin Aşağı Maraş bölgesinde yer alan Pertev Paşa mahallesinde yaşayan insanların sosyo-kültürel ve sosyo-ekonomik kimliğini incelemek ve bu kimlik ile fiziksel çevre bağlantısını ortaya koymak için yapılmıştır. Kıbrıs adasındaki siyasi belirsizlikler adaya ve adadaki yerleşim alanlarına pek çok sosyal ve fiziksel gerilimler ve belirsizlikler getirmistir. Kentsel tasarımın fiziksel çevre yanında sosyal, ekonomik ve kültürel alanlardaki sorunlara da çözüm üretebilen çok boyutlu bir disiplin olduğu bilinciyle, bu çalışma, seçilen kentsel alanın daha yaşanabilir bir mekana dönüştürülmesi için, orada yaşayanların sosyo-ekonomik gereksinimlerini göz önünde bulundurarak bazı tasarım ve iyileşme önerileri geliştirmiştir. Bunun yanında, söz konusu alanda yaşayan halkın, adada herhangi bir çözüm sonrasında yer değiştirmek durumunda kalması durumunda, nasıl bir yeni yerleşim alanında yaşamalarının uygun olabileceği konusu da, yine kentsel tasarım prensipleri ile halkın gereksinimleri göz önüne alınarak bu araştırmanın kapsamında yer almıştır. Araştırma sürecinde veri toplama teknikleri olarak, literatür araştırması, anket, bire bir görüşme, alan çalışması ve gözlem teknikleri kullanılmıştır. Çalışma sonucunda, Pertev Paşa mahallesindeki kentsel çevrenin, sosyal, ekonomik ve fiziksel kimlik degerlendirmesine dayanarak, Aşağı Maraş’in gelecekteki gelişiminde meydana gelebilecek iki farklı senaryoya dayalı olarak görüş ve öneriler sunulmuştur. Anahtar Kelimeler: Kimlik, sosyo-kültürel ve sosyo-ekonomik çalışmalar, kentsel tasarım, Pertev Paşa, Aşağı Maraş, Gazimağusa, Kuzey Kıbrıs
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Supervisor: Prof. Dr. Şebnem Önal Hoşkara.
Keywords: Architecture; Urban Design; Urban Design- Space (Architecture) - Pertev Paşa; District- Famagusta (Cyprus, North; Identity; Socio-culture; Socio-economy; urban design; Pertev Pasa; Asagi Maras; Famagusta; North Cyprus